(3GdGSJKeGQ GdRQGYj SHjd dJMbjb GdCef GdZPGFjs (3GdLRGFQ QDjI GSJQGJjLjIs - (3SYjL(B, (3ehfjQI s ((3GdLRGFQs (3OGQ CLjGd GdQbej s, 2024)
(3jJfGhd GdcJGH JWhQ GdCgejI GdGSJQGJjLjI ddbWGY GdRQGYj hJCKjQ GdGSJKeGQ Ydi eMGhQ GdCef GdZPGFj aj GdLRGFQ NdGd GdaJQI(B2000-2017(3, QDjI GSJQGJjLjI fMh JaYjd GdGSJKeGQ GdRQGYj dJMbjb GdCef GdZPGFj aj GdLRGFQ(B. s
Keywords: (3GdGSJKeGQs; (3GdCef GdZPGFjs; (3GdRQGYI (B-(3GbJUGOjGJ s